The Effect of Financial Literacy on Academic Achievement: Financial Management as A Mediation Variable - Septiani, Putri; Helmi, Sulaiman; Gunarto, Muji (Novatio : Journal of Management Technology and Innovation, 2024)
This study is motivated by the importance of financial literacy in students' lives, especially in influencing their academic performance. Students with a good understanding of financial literacy tend to be more able to manage finances effectively, contributing to better academic achievement. This study aims to analyze the effect of financial literacy on student academic achievement: financial management as a mediating variable. The approach used in this research is quantitative using a survey method. The research sample consisted of 100 active students of Bina Darma University, who were selected using a non-probability sampling technique. Data was processed using Structural Equation Modeling (SEM) analysis through SmartPLS 4.0. The results showed that (1) financial literacy has a significant effect on student academic achievement, (2) financial literacy has a significant effect on financial management, (3) financial management has a significant effect on student academic achievement, and (4) financial management acts as a mediating variable in the relationship between financial literacy and student academic achievement. This finding confirms that an increase in financial literacy must be accompanied by good financial management skills to positively impact students' academic performance. Therefore, universities are expected to provide more intensive financial education to help students manage their finances more effectively.